Investigating Literal and Inferential Comprehension Achievement of Grade Six Students - Sulfa, Sulfasyah; Ernawati, Ernawati; Fatmawati, Fatmawati (Technium Social Sciences Journal, 2023)
Literal and inferential comprehension questions characterize the types of tasks students typically complete in reading assignments in elementary schools in Indonesia. This study, a preliminary survey of more extensive research, aimed at describing Grade Six students’ literal and inferential comprehension achievements. The research respondents were 198 Grade Six students from three elementary schools in Makassar, Indonesia. The research instrument used was a reading comprehension test which consisted of 35 multiple-choice questions. The data obtained were tabulated and analyzed descriptively using percentage analysis. The results of the study showed that most of the students in this study had low achievement in reading comprehension, both in literal and inferential comprehension. The research findings had an implication for the teaching and learning process of reading comprehension in Grade Six in elementary schools in Indonesia and other similar contexts.